If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 2 = 7x + 65 Reorder the terms: 2 + -2x = 7x + 65 Reorder the terms: 2 + -2x = 65 + 7x Solving 2 + -2x = 65 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + -2x + -7x = 65 + 7x + -7x Combine like terms: -2x + -7x = -9x 2 + -9x = 65 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + -9x = 65 + 0 2 + -9x = 65 Add '-2' to each side of the equation. 2 + -2 + -9x = 65 + -2 Combine like terms: 2 + -2 = 0 0 + -9x = 65 + -2 -9x = 65 + -2 Combine like terms: 65 + -2 = 63 -9x = 63 Divide each side by '-9'. x = -7 Simplifying x = -7
| 7m(2m-12)=0 | | -1+6x=-3x+8 | | 2(4x+2)+9x= | | 50/x=3 | | 90=3x+5x-6 | | ln(x)-ln(4)=0 | | (7+5x)-5x= | | ln(x)-on(4)=0 | | -25=5(3g+4) | | (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) | | 9x^4-19x^2-2=0 | | -3+x=6n+22 | | -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) | | -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n |